Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

Facile synthesis of 1,3-thiazolidin-4-ones as antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Arkile, Manisha A.; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
We have developed, highly efficient, one-pot, solvent-free, [Et3NH][HSO4] catalyzed multicomponent reaction protocol for the synthesis of 1,3-thiazolidin-4-ones in excellent yields. For the first time, the 1,3-thiazolidin-4-ones were evaluated in vitro for their antimycobacterial activity against Mycobacterium tuberculosis dormant MTB H37Ra and Mycobacterium bovis BCG strains. Among the synthesized basic 1,3-thiazolidin-4-ones, particularly the compounds 4c, 4d, 4e, 4f, 4h, 4i and 4j displays promising antitubercular activity along with no significant cytotoxicity against the cell lines MCF-7, A549 and HCT-116. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular; Cytotoxicity; Green protocol; Multicomponent reaction

Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Ferric oxide nanocatalyst: synthesis, characterization, and application in the one-pot three-component synthesis of 3,4,5-trisubstituted isoxazole derivatives - Totre, Ganesh; Shinde, Dnyaneshwar; Shirsath, Sachin; Patil, Prakash; Kulkarni, Pramod (Monatshefte Fur Chemie, 2024)
In this study, we have focused on the preparation and application of a nano-ferric oxide catalyst as a heterogeneous catalyst in the one-pot, three-component synthesis of isoxazole derivatives. The ferric oxide catalyst was synthesized using a simple precipitation method and thoroughly characterized using techniques such as FT-IR, XRD, SEM, EDX, and BET. The effectiveness of the ferric oxide catalyst as a heterogeneous catalyst was investigated in the synthesis of 3,4,5-trisubstituted isoxazole. The results of the synthesis demonstrated that the catalyst exhibited high efficiency in facilitating the three-component, one-pot synthesis of 3,4,5-trisubstituted isoxazole derivatives. The synthesis route employed in this study offers several advantages, including its simplicity, ease of workup, and environmental friendliness. Furthermore, the catalyst was successfully recovered and reused for five cycles without experiencing a significant loss in catalytic activity. This finding highlights the excellent stability and promising potential of the catalyst for organic transformations. Overall, our study showcases the successful preparation and application of the nano-ferric oxide catalyst in the synthesis of isoxazole derivatives, providing valuable insights into its catalytic performance and potential for future applications in organic chemistry.
Keywords: Ferric oxide nanoparticles; heterogeneous catalyst; Isoxazole; Multicomponent reaction

N-SO3H functionalised brønsted acidic ionic liquid catalysed sequential one-pot synthesis of 2-amino-3-cyanopyridines via claisen-schmidt condensation under solvent-free condition - Das, Sukanya; Paul, Subham; Kashyap, Niharika; Saikia, Pinku; Borah, Ruli (Chemistryselect, 2024)
This work presents a simple approach for the synthesis of 2-amino-3-cyanopyridines via a one pot two-step sequential route catalysed by direct N–SO3H functionalised Br & oslash;nsted acidic ionic liquids (BAILs). Herein, catalytic activities of four BAILs namely ([TSPi][Cl](2), [DSIM][TFA], [EDSIM][TFA] and [DBDSA][TFA]) were explored and among them [TSPi][Cl](2) was found to be the most efficient reusable homogeneous catalyst. This process involves the ionic liquid catalysed in situ generation of chalcones from Claisen-Schmidt condensation between aromatic aldehydes and acetophenone/4-Cl acetophenone, followed by multicomponent reaction (MCR) with malononitrile and ammonium acetate using the same IL catalyst to selectively produce 2-amino-3-cyanopyridine derivatives in a solvent-free medium at 80 degrees C within 30-60 minutes in high yields (96-86 %). This amalgamation of MCR with ionic liquids and solvent-free conditions makes the present work more compliant with the protocols of Green Chemistry.
Keywords: 2-amino-3-cyanopyridines; Bronsted acidic ionic liquids; chalcones; Multicomponent reaction; One-pot approach